2001
DOI: 10.1128/mmbr.65.3.422-444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Context and Possible Physiological Themes of ς54-Dependent Genes inEscherichia coli

Abstract: SUMMARY ς54 has several features that distinguish it from other sigma factors in Escherichia coli: it is not homologous to other ς subunits, ς54-dependent expression absolutely requires an activator, and the activator binding sites can be far from the transcription start site. A rationale for these properties has not been readily apparent, in part because of an inability to assign a common physiological function for ς54-dependent genes. Surveys of ς54-dependent genes from a variety of organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
308
1
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(330 citation statements)
references
References 171 publications
(343 reference statements)
13
308
1
8
Order By: Relevance
“…glnHPQ codes for components of a high affinity glutamine transport system (43,44); nac for a regulator of several Ntr genes (44); and ygjG for putrescine transaminase (45,46). The promoters for these operons, except for glnA-ntrBC, were fused to lacZ and expressed on the chromosome.…”
Section: Alteration Of Surface Residues Of the B-helix Of The C-terminalmentioning
confidence: 99%
“…glnHPQ codes for components of a high affinity glutamine transport system (43,44); nac for a regulator of several Ntr genes (44); and ygjG for putrescine transaminase (45,46). The promoters for these operons, except for glnA-ntrBC, were fused to lacZ and expressed on the chromosome.…”
Section: Alteration Of Surface Residues Of the B-helix Of The C-terminalmentioning
confidence: 99%
“…However, the homologues with the lowest expression levels (chrA1a and chr1NCa), both from chromosome 1, were predicted to possess promoters regulated by s 54 factors. The fact that s 54 controls the transcription of genes devoted to a variety of functions (Reitzer & Schneider, 2001) suggests that these chr genes might express under conditions distinct from those tested in this work. This proposal is supported by the finding that chrA1a and chr1NCa genes conferred clear chromate resistance phenotypes when assayed in E. coli.…”
Section: Discussionmentioning
confidence: 93%
“…In a paper by Reitzer & Schneider (2001), the authors mentioned unpublished results of experiments in which it was not possible to demonstrate the existence of a transcript from the P6 promoter in nitrogen-limited cells, which meant NtrC was not the activator of this transcription. We confirm this opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the upstream sequence of the rpoH gene by a BLAST search showed that the s 54 promoter was correctly situated according to the rules proposed by Reitzer & Schneider (2001) for active s 54 promoters. Moreover, an IHF-binding site homologous to the consensus sequence was found at the position 2349 to 2362 (Fig.…”
Section: Analysis Of the Promoter Region Of The Rpoh Genementioning
confidence: 99%
See 1 more Smart Citation